2016
DOI: 10.1007/s10878-016-0022-z
|View full text |Cite
|
Sign up to set email alerts
|

Convex median and anti-median at prescribed distance

Abstract: The status of a vertex v in a connected graph G is the sum of the distances between v and all the other vertices of G. The subgraph induced by the vertices of minimum (maximum) status in G is called median (anti-median) of G. Let H = (G 1 , G 2 , r ) denote a graph with G 1 as the median and G 2 as the anti-median of H , d(G 1 , G 2 ) = r and both G 1 and G 2 are convex subgraphs of H . It is known that (G 1 , G 2 , r ) exists for every G 1 , G 2 with r ≥ diam(G 1 )/2 + diam(G 2 )/2 + 2. In this paper we show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
0
0
Order By: Relevance
“…Given a G the issue of tracking down a H to such an extent that M(H) ≅G is alluded to as the median issue. In [6], it is shown that any G = (V, E) is the median of some associated. In [3] the thought of against median of a was presented and demonstrated that each is the counter median of some.…”
Section: Introductionmentioning
confidence: 99%
“…Given a G the issue of tracking down a H to such an extent that M(H) ≅G is alluded to as the median issue. In [6], it is shown that any G = (V, E) is the median of some associated. In [3] the thought of against median of a was presented and demonstrated that each is the counter median of some.…”
Section: Introductionmentioning
confidence: 99%